Frames of cooperation : interactional dynamics of pandemic governance networks - Kork, Anna-Aurora; Paananen, Henna; Kihlström, Laura; Tynkkynen, Liina-Kaisa (Taylor & Francis, 2025)
Cooperation and interaction are essential in governance networks (GNs), yet how they manifest in practice remains unclear. This study explores cooperation within GNs, focusing on interactional dynamics that shape horizontal policymaking during pandemic governance. Using an inductive frame analysis approach, we examine governance interactions through interviews from Finland’s COVID-19 response. We identify four frames of cooperation that reveal how divergent framings represent joint policymaking. The findings expose cooperation realities, expectations, and interactional challenges, illustrating dynamics in network integrity and joint problem-solving. This study contributes to practice-oriented GN research with insights into how actors navigate cooperation in complex, multi-actor governance systems.
Keywords: Cooperation; governance network; frame analysis; COVID-19; complexity; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|